Nonlinear seismic response of a masonry arch bridge - Sayin, Erkut (Techno-Press, 2016)
Historical structures that function as a bridge from past to present are the cultural and social reflections of societies. Masonry bridges are one of the important historical structures. These bridges are vulnerable against to seismic action. In this study, linear and non-linear dynamic analyses of historical Nadir Bridge are assessed. The bridge is modelled with three dimensional finite elements. For the seismic effect, artificial acceleration records are generated considering the seismic characteristics of the region where the bridge is located. Seismic response of the bridge is investigated.
Keywords: masonry bridges; finite element model; linear and non-linear dynamic analysis; seismic response